Piłka nożna i rekonstrukcje niemieckiej tożsamości narodowej - Melosik, Zbyszko (Kultura-Społeczeństwo-Edukacja, 2016)
The article is aimed at analysing the relationship between football and ways of reconstructing the German national identity. At the beginning the origin of football in Germany is decribed. Than the role of „Berno Miracle” (German world championship in 1954) in creation the postwar new German identity is considered as well as the role of football in presenting „new Germany” to the world in the 2006 world championship organized by Germany. At the end the stereotypes considering the connections between German style of play and German „national character” are presented.